Phenolic Profile and Antioxidant Activity of Extracts Prepared from Fermented Heat‐Stabilized Defatted Rice Bran. Issue 11 (11th October 2014) - Webber, Daniel M.; Hettiarachchy, Navam S.; Li, Ruiqi; Horax, Ronny; Theivendran, Sivarooban
Abstract Heat‐stabilized, defatted rice bran (HDRB) serves as a potential source of phenolic compounds which have numerous purported health benefits. An estimated 70% of phenolics present in rice bran are esterified to the arabinoxylan residues of the cell walls. Release of such compounds could provide a value‐added application for HDRB. The objective of this study was to extract and quantify phenolics from HDRB using fermentation technology. Out of 8 organisms selected for rice bran fermentation, Bacillus subtilis subspecies subtilis had the maximum phenolic release of 26.8 mg ferulic acid equivalents (FAE) per gram HDRB. Response surface methodology was used to further optimize the release of rice bran phenolics. An optimum of 28.6 mg FAE/g rice bran was predicted at 168 h, 0.01% inoculation level, and 100 mg HDRB/mL. Fermentation of HDRB for 96 h with B. subtilis subspecies subtilis resulted in a significant increase in phenolic yield, phenolic concentration, and radical scavenging capacity. Fermented rice bran had 4.86 mg gentistic acid, 1.38 mg caffeic acid, 6.03 mg syringic acid, 19.02 mg (‐)‐epicatechin, 4.08 mg p‐courmaric acid, 4.64 mg ferulic acid, 10.04 mg sinapic acid, and 17.59 mg benzoic acid per 100 g fermented extract compared to 0.65 mg p‐courmaric acid and 0.36 mg ferulic acid per 100 g nonfermented extract. The high phenolic content and antioxidant activity of fermented HDRB extract indicates that rice bran fermentation under optimized condition is a potential means of meeting the demand for an effective and affordable antioxidant.